STRUCTURAL ANALYSIS OF INDICATORS OF QUALITY OF CONSTRUCTION AND REPAIR MACHINERY OF THE STATE SPECIAL SERVICE OF TRANSPORT OF THE MINISTRY OF TRANSPORT AND COMMUNICATIONS OF UKRAINE - Kramar, I. Ye.; Yakovliev, S. O.; Sytyk, V. V. (Science and Transport Progress, 2005)
The article gives estimation of technical level of building and handling machinery, on the basis of which it develops a method of technical equipment of the State Special Transport Service of the Ministry of Transport and Communication of Ukraine and provides practical recommendations thereto.